Effects of activation of the LINE-1 antisense promoter on the growth of cultured cells - Tomoyuki Honda (Nature Portfolio, 2020)
Abstract Long interspersed element 1 (LINE-1, or L1) is a retrotransposon that constitutes ~ 17% of the human genome. Although ~ 6000 full-length L1s spread throughout the human genome, their biological significance remains undetermined. The L1 5′ untranslated region has bidirectional promoter activity with a sense promoter driving L1 mRNA production and an antisense promoter (ASP) driving the production of L1-gene chimeric RNAs. Here, we stimulated L1 ASP activity using CRISPR-Cas9 technology to evaluate its biological impacts. Activation of the L1 ASP upregulated the expression of L1 ASP-driven ORF0 and enhanced cell growth. Furthermore, the exogenous expression of ORF0 also enhanced cell growth. These results indicate that activation of L1 ASP activity fuels cell growth at least through ORF0 expression. To our knowledge, this is the first report demonstrating the role of the L1 ASP in a biological context. Considering that L1 sequences are desilenced in various tumor cells, our results indicate that activation of the L1 ASP may be a cause of tumor growth; therefore, interfering with L1 ASP activity may be a potential strategy to suppress the growth.